Extra-Articular Fascial Strip Repair of the Cranial Cruciate Deficient Stifle: Technique and Results in Seven Dogs - Aiken, S. W.; Bauer, M. S.; Toombs, J. P. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
An extra-articular fascial strip technique, for stabilization of the cranial cruciate deficient stifle, is described and evaluated in a series of seven dogs suffering from rupture of the cranial cruciate ligament. The technique was easily performed and resulted in normal stifle joint bio-mechanics, as determined by evaluation of the instantaneous centre of motion. Cranial drawer motion was eliminated immediately after the operation and, after a partial loss of stability at four weeks, six stifles had normal or possessed less than 3.0 mm of cranial drawer motion in either flexion or extension at 26 weeks after the operation. At subsequent examinations, six dogs were free of clinical lameness, and one had a mild intermittent lameness with exercise at 26 weeks after the operation. The extra-articular fascial strip technique is an alternative to lateral retinacular suture techniques for stabilization of the cranial cruciate deficient stifle in dogs weighing less than 15 kg.An extra-articular fascial strip technique for stabilization of the cranial cruciate deficient stifle is described and evaluated. The technique was easily performed and resulted in normal stifle joint biomechanics, as determined by evaluation of the instantaneous centre of motion. All of the dogs performed well and six of seven were free of lameness 26 weeks after the operation.
Keywords: Cruciate ligament; extra-articular repair; fascial strip; instant centre of motion